Krisis COVID-19 dan Respons Administrasi Publik: Pelajaran yang Dipetik dari Penanganan Pandemi - Solichin, Solichin; Faridah, Faridah; Fathia, Nur Bella; Wulandari, Septi (SENGKUNI Journal (Social Science and Humanities Studies), 2021)
The COVID-19 crisis has become a global challenge that requires a rapid and adaptive public administration response. This article analyzes lessons learned from governments' handling of pandemics around the world. The main focus is on the role of information technology, inter-agency collaboration, health system resilience, policy innovation, and psychological and social factors in the context of public administration responses. The research involved a comprehensive analysis of various policies and strategies implemented by governments at various levels. The results show that information technology, such as contact tracing apps and online platforms, plays a vital role in mitigating the spread of the virus and providing accurate information to the public. Inter-agency and intersectoral collaboration proved to be a decisive factor in the success of the public administration's response. Health system resilience was highlighted, and countries with strong health systems tended to be more successful in providing adequate health services. Policy innovations, including coordinated lockdowns, mass vaccinations and economic support for affected citizens, have proven effective in addressing the socio-economic impacts of the pandemic.People's psychological and social factors play an important role in the success of government policies. Communication strategies that build trust, manage public concerns, and motivate compliance with precautionary measures have proven crucial in easing panic and increasing public support.This article not only identifies lessons learned from handling the COVID-19 pandemic, but also provides suggestions for strengthening the resilience and adaptability of public administration systems in the future. The implications of these findings are expected to help governments and stakeholders prepare for similar challenges in the future.